Epiphytic lactic acid bacteria succession during the pre-ensiling and ensiling periods of alfalfa and corn - Chunjian Lin; B.E. Brent; K.K. Bolsen; Daniel Y.C. Fung (Kansas Agricultural Experiment Station Research Reports, 1992)
Twenty three species and 306 strains of epiphytic lactic acid bacteria (LAB) were found for two cuttings of alfalfa, each harvested at three stages of maturity, and three whole-plant corn hybrids. Epiphytic LAB counts were low and variable on the standing crops, particularly on alfalfa. Wilting increased LAB numbers slightly for alfalfa, but the chopping process increased counts dramatically for both crops. Lactobacillus plantarum, Pediococcus pentosaceus, Enterococcus faecium, and E. faecalis were predominant on both standing crops. The changes in LAB caused by wilting or chopping were mainly proportional changes in the four dominant species. Once the crops were ensiled, total LAB counts increased rapidly, reached a maximum within 1 day, and then declined after 7 days of fermentation. Enterococcus species decreased sharply or disappeared during the early fermentation. The species most prominent through day 7 were L. plantarum and P. pentosaceus. After 7 days, more species, i.e., L. homohiochii, L. brevis, and L. gasseri, joined the succession and became prevalent, depending on the crop. Only two of the six alfalfa silages were adequately preserved, whereas all three corn hybrids fermented normally. No relationship was found between epiphytic LAB numbers or species and adequacy of fermentation. Neither were pH changes during the fermentation explained by the epiphytic LAB count or population succession. Rather, the well-fermented alfalfa silages were those ensiled at a high dry matter (DM) content (>36%) and low buffering capacity (/kg of DM). Only a few of the LAB strains were consistently present, thus indicating that populations changed during fermentation to fit an ecological niche.
Keywords: Cattlemen' s Day; 1992; Kansas Agricultural Experiment Station contribution; no. 92-407-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 651; Beef; Epiphytic lactic acid bacteria; Alfalfa; Corn; Silage